Acceptability and feasibility of a computer-based application to help Aboriginal and Torres Strait Islander Australians describe their alcohol consumption. Issue 1 (1st February 2021) - Lee, Ks Kylie; Conigrave, James H.; Al Ansari, Mustafa; Wilson, Scott; Perry, Jimmy; Zheng, Catherine; Freeburn, Bradley; Room, Robin; Callinan, Sarah; Hayman, Noel; Chikritzhs, Tanya; Slade, Tim; et al.
Abstract: We examined acceptability and feasibility of a tablet application ("App") to record self-reported alcohol consumption among Aboriginal and Torres Strait Islander Australians. Four communities (1 urban; 3 regional/remote) tested the App, with 246 adult participants (132 males, 114 females). The App collected (a) completion time; (b) participant feedback; (c) staff observations. Three research assistants were interviewed. Only six (1.4%) participants reported that the App was "hard" to use. Participants appeared to be engaged and to require minimal assistance; nearly half verbally reflected on their drinking or drinking of others. The App has potential for surveys, screening, or health promotion.